RADT-04. SINGLE SESSION GAMMA KNIFE RADIOSURGERY TO TREAT PATIENTS WITH 20 OR MORE BRAIN METASTASES. (14th November 2022) - Wei, Zhishuo; Luy, Diego; Yavan, Sila; Jose, Shalini; Worrell, Stephen; Belkhir, J Raouf; Deng, Hansen; Niranjan, Ajay; Lunsford, L Dade
Abstract: BACKGROUND: Stereotactic Radiosurgery (SRS) has become a primary management option for brain metastases (BMs). This present study aims to review outcomes in patients with ≥ 20 BMs treated in a single session SRS and to identify predictors of local tumor control (LTC) and overall survival (OS). METHODS: We identified 75 patients including 26 non-small cell lung cancer (NSCLC), 21 small cell lung cancer (SCLC), 14 breast cancer (BC), and 14 melanoma patients who underwent SRS for ≥ 20 BMs between 2014 and 2020. The median number of tumors was 24 (range 20 – 52), and the median cumulative tumor volume was 3.70 cc (0.13 – 62.49 cc). The median margin dose was 16 Gy (14 – 20 Gy). Median skull integral dose was 5492 mJ (range 1372 – 11243 mJ). The median treatment time for each session was 160 min. Outcome variables were assessed using univariate and multivariate analyses with p < 0.05. RESULTS: Median OS after SRS was 5.8 months (range 0.1 – 73.2 months). Primary cancer type and concurrent immunotherapy were significant predictive factors for patient OS after SRS (p = 0.01, 0.05, and 0.02, respectively). LTC rate at 6 and 12 months after SRS was 95.7% and 83.7%, respectively. Thirty (40.0%) patients underwent additional SRS and 3 patients (4%) received post-SRS WBRT due to distant tumor recurrence. The median time to distant recurrence was 5 months (range 2-28 months). SRS-induced adverse radiation effects (ARE) events were observed in 3 patients (4.0%; 1 NSCLC, 1 SCLC, and 1 melanoma). CONCLUSIONS: Our results suggest that patients with ≥ 20 BMs can be safely treated with SRS with an excellent LTC rate and a low risk of ARE. Newly developed BMs can be treated with repeat SRS. This single-session SRS allows patients to proceed with systemic cancer care without interruption.